An analysis of attitudes and socio-cultural patterns reflected in selected short stories of F. Sionil Jose and Edilberto K. Tiempo as an instrument in the development of appreciation for and understanding of the Filipino culture - Pascua, Origen Pidut (1973)
It was the study's goal to determine the attitudes and socio-cultural patterns reflected in selected short stories of Edilberto K. Tiempo and F. Sionil Jose. This study also aimed to discover the major categories of events and scenes that would provide insights into the understanding of the Filipino culture and society. The stories were selected because of the following reasons: awards and honors, culture thematic content, individual author's position and Philippine outlook. Analysis and discussion of the data on attitudes and socio-cultural patterns revealed that literature particularly the short story is a rich repository of culture components and any study undertaken on them reveals these aspects which are important in the teaching of culture in language classes.